Transcriptome Analysis of Pepper (Capsicum annuum) Revealed a Role of 24-Epibrassinolide in Response to Chilling - Li, Jie; Yang, Ping; Kang, Jungen; Gan, Yantai; Yu, Jihua; Calderón-Urrea, Alejandro; Lyu, Jian; Zhang, Guobin; Feng, Zhi; Xie, Jianming (Frontiers in Plant Science, 2016)
Brassinosteroids (BRs) have positive effects on many processes during plant growth, development, and various abiotic stress responses. However, little information is available regarding the global gene expression of BRs in response to chilling stress in pepper. In this study, we used RNA sequencing to determine the molecular roles of 24-epibrassinolide (EBR) during a chilling stress response. There were 39,829 transcripts, and, among them, 656 were differently-expressed genes (DEGs) following EBR treatment (Chill+EBR) compared with the control (Chill only), including 335 up-regulated and 321 down-regulated DEGs. We selected 20 genes out of the 656 DEGs for RT-qPCR analysis to confirm the RNA-Seq. Based on GO enrich and KEGG pathway analysis, we found that photosynthesis was significantly up-enriched in biological processes, accompanied by significant increases in the net photosynthetic rate (Pn), Fv/Fm and chlorophyll content. Furthermore, the results indicate that EBR enhanced endogenous levels of salicylic acid (SA) and jasmonic acid (JA) while suppressing the ethylene (ETH) biosynthesis pathway, suggesting that BRs function via a synergistic cross-talk with SA, JA and ETH signaling pathways in response to chilling stress. In addition, EBR induced cellulose synthase-like protein and UDP-glycosyltransferase, suggesting a contribution to the formation of cell wall and hormone metabolism. EBR also triggered the calcium signaling transduction in cytoplasm, and activated the expression of cellular redox homeostasis related genes, such as GSTX1, PER72, and CAT2. This work, therefor, identified the specific genes showed different expression patterns in EBR-treated pepper and associated with the processes of hormone metabolism, redox, signaling, transcription and defense. Our study provides the first evidence of the potent roles of BRs, at the transcription level, to induce the tolerance to chilling stress in pepper as a function of the combination of the transcriptional activities, signaling transduction, and metabolic homeostasis.